Automated electrical source imaging with scalp EEG to define the insular irritative zone: Comparison with simultaneous intracranial EEG. Issue 12 (December 2021) - Iachim, Evelina; Vespa, Simone; Baroumand, Amir G.; Danthine, Venethia; Vrielynck, Pascal; de Tourtchaninoff, Marianne; Fierain, Alexane; Ribeiro Vaz, Jose Geraldo; Raftopoulos, Christian; Ferrao Santos, Susana; van Mierlo, Pieter; El Tahry, Riëm
Highlights: Ictal or interictal epileptiform discharges originating in the insula are difficult to be detected by scalp EEG. We evaluated the accuracy of automated low density electrical source imaging (ESI) to define the insular irritative zone by comparing ESI results with concomitant stereo-EEG. ESI showed 53% overall accuracy, 55% specificity and 53% sensitivity and might be a useful tool in presurgical evaluation. Abstract: Objective: To evaluate the accuracy of automated interictal low-density electrical source imaging (LD-ESI) to define the insular irritative zone (IZ) by comparing the simultaneous interictal ESI localization with the SEEG interictal activity. Methods: Long-term simultaneous scalp electroencephalography (EEG) and stereo-EEG (SEEG) with at least one depth electrode exploring the operculo-insular region(s) were analyzed. Automated interictal ESI was performed on the scalp EEG using standardized low-resolution brain electromagnetic tomography (sLORETA) and individual head models. A two-step analysis was performed: i) sublobar concordance between cluster-based ESI localization and SEEG-based IZ; ii) time-locked ESI-/SEEG analysis. Diagnostic accuracy values were calculated using SEEG as reference standard. Subgroup analysis was carried out, based on the involvement of insular contacts in the seizure onset and patterns of insular interictal activity. Results: Thirty patients were included in the study. ESI showed an overall accuracy of 53% (C.I. 29–76%). Sensitivity and specificity were calculated as 53% (C.I. 29–76%), 55% (C.I. 23–83%) respectively. Higher accuracy was found in patients with frequent and dominant interictal insular spikes. Conclusions: LD-ESI defines with good accuracy the insular implication in the IZ, which is not possible with classical interictal scalp EEG interpretation. Significance: Automated LD-ESI may be a valuable additional tool to characterize the epileptogenic zone in epilepsies with suspected insular involvement.